Efektivitas Penggunaan Media Pembelajaran Berbasis Digital dalam Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran IPAS di Sekolah Dasar - Afdal Kurniawan; Adrias Adrias; Salmaini Safitri Syam (International Forum of Researchers and Lecturers, 2025)
This study aims to comprehensively examine the effectiveness of digital learning media in enhancing students' motivation in the subject of Natural and Social Sciences (IPAS) at the elementary school level. Utilizing a qualitative approach based on a literature review, this study analyzes various academic references regarding the use of digital technology in the learning process. The findings indicate that digital media, such as educational videos, interactive simulations, and technology-based applications, significantly contribute to increasing student engagement and learning enthusiasm. The success of digital media in education is supported by several key factors, including active student participation, real-time feedback, and the presentation of materials that are more dynamic, diverse, and responsive to individual student needs. Moreover, digital learning approaches allow for a more flexible, engaging learning process that adapts to students’ learning styles. Thus, based on the conducted analysis, it can be concluded that integrating digital technology into IPAS instruction holds great potential as an innovative pedagogical strategy.